The use of smartphone photography on mobile teledentistry for caries examination in epidemiological surveys: a systematic review - Adilah, Bunga Hasna; Rahardjo, Anton; Bahar, Armasastra (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2023)
ABSTRACTIntroduction: Direct clinical examination has been the gold standard for screening dental caries; however, due to its various limitations, teledentistry has been developed as an alternative screening method for a remote dental caries examination. Mobile teledentistry is one of the telemedicine developments that employ smartphone photography technology because it is user-friendly, reasonably affordable, and portable. The purpose of this systematic review is to see how smartphone photography on mobile teledentistry is used as an alternative tool for caries examination in epidemiological surveys, and whether smartphone photography on mobile teledentistry is an accurate and reliable tool for dental caries examination in an epidemiological survey. Methods: Data collection was according to the PRISMA statement guidelines. Articles were screened from various literature published in the last 10 years, which were searched through the PubMed, ProQuest, and Science Direct databases. The selection of articles was adjusted according to the PICOS formula. The feasibility and quality tests of the included research articles were carried out using the CEBM criteria for Diagnostic Accuracy research. Results: There were six research publications out of 242 search results that were related to smartphone photography in mobile teledentistry for caries examination in dental screening. The studies showed high levels of sensitivity, specificity and accuracy (>80%) as well as fairly good reliability (Kappa>0.81). Caries examination using smartphone photography method has weaknesses, such as variations in the quality of intra-oral photos and the inability of photos to detect caries in certain locations. Conclusion: Smartphone photography on mobile teledentistry is a sensitive and reliable tool as an alternative for caries examination in epidemiological surveys. However, several factors such as the photography technique, the quality of light and the camera operator’s skills need to be taken into consideration because they can affect the results of caries examination.KEY WORDS: Smartphone photography, mobile teledentistry, caries examination, caries screeningPenggunaan smartphone photography pada mobile teledentistry untuk pemeriksaan karies pada survey epidemiologi: systematic reviewABSTRAKPendahuluan: Pemeriksaan klinis secara langsung telah menjadi gold standard untuk skrining karies; namun, karena keterbatasannya, teledentistry mulai dikembangkan sebagai metode alternatif untuk pemeriksaan karies jarak jauh. Mobile teledentistry merupakan salah satu pengembangan dari telemedicine yang memanfaatkan teknologi smartphone photography karena mudah digunakan, relatif murah, dan dapat dibawa kemana saja. Tujuan ulasan sistematis ini adalah melihat bagaimana penggunaan smartphone photography pada mobile teledentistry sebagai alat alternatif untuk pemeriksaan karies pada survei epidemiologi, serta apakah smartphone photography pada mobile teledentistry merupakan alat yang akurat dan reliable untuk pemeriksaan karies pada survey epidemiologi. Metode: Pengumpulan data dalam penulisan ulasan sistematis sesuai dengan pedoman PRISMA statement. Penjaringan artikel dari berbagai literatur yang diterbitkan 10 tahun terakhir, yang dicari melalui database PubMed, ProQuest, dan Science Direct. Pemilihan artikel disesuaikan dengan formula PICOS. Uji kelayakan dan kualitas studi artikel penelitian yang diinklusikan dilakukan menggunakan kriteria CEBM untuk penelitian Diagnostic Accuracy. Hasil: Terjaring 6 artikel penelitian dari total 242 artikel yang didapatkan terkait dengan smartphone photography pada mobile teledentistry untuk pemeriksaan karies pada skrining gigi dan mulut. Penelitian menunjukkan tingkat sensitivitas, spesifisitas, dan akurasi yang tinggi (>80%) serta reliabilitas yang cukup baik (Kappa>0,81). Pemeriksaan karies dengan metode smartphone photography memiliki kelemahan diantaranya variasi kualitas foto intra oral dan ketidakmampuan foto untuk mendeteksi karies pada lokasi tertentu. Simpulan: Smartphone photography pada mobile teledentistry merupakan alat yang sensitif dan dapat diandalkan sebagai alternatif untuk pemeriksaan karies pada survei epidemiologi. Beberapa faktor, seperti teknik pengambilan foto, kualitas pencahayaan dan kemampuan operator perlu diperhatikan karena dapat mempengaruhi hasil pemeriksaan karies.KATA KUNCI: Smartphone photography, mobile teledentistry, pemeriksaan karies, skrining